Full Mouth Reconstruction of a Bruxer with Severely Worn Dentition: A Clinical Report - Somayeh Zeighami; Hakimeh Siadat; Sakineh Nikzad (Case Reports in Dentistry)
Tooth wear is attributed to several factors many of which often remain unidentified. Management of tooth wear is challenging in preventive and restorative dentistry. Correct assessment of occlusal vertical dimension, interocclusal rest space, and centric relation records are critical for successful treatment. In order to evaluate different treatment modalities and select the treatment of choice some information can be obtained from study casts and diagnostic wax-up. In order to achieve a predictable and desirable result, a systematic approach may be helpful. This paper describes the full mouth rehabilitation of a 36-year-old bruxer with severely worn dentition and other dental problems such as unfavorable restorations. A diagnostic work-up was performed and provisional restorations were made; then, they were clinically evaluated and adjusted based on the criteria dictating esthetics, phonetics, and vertical dimension. After endodontic therapy, clinical crown lengthening was performed. Two short implants were inserted in the posterior mandible. Custom-cast dowel cores and metal-ceramic restorations were fabricated and a full occlusal splint was used to protect the restorations. We ensured stable contacts on all teeth with equal intensity in centric relation and anterior guidance in accord with functional jaw movements.